PERAN KELUARGA DALAM PERAWATAN PENDERITA TUBERKULOSIS PARU DI KECAMATAN GAPURA KABUPATEN SUMENEP - Mujib Hannan; Syaifurrahman Hidayat (Fakultas Ilmu Kesehatan, 2013)
Background: tuberculosis diseases is still suffered by the Indonesia citizens and is the public health problem which is quite large. Pulmonary tuberculosis patients with BTA (+) in 2009 amounted to 1256 persons. In 2010 was increased up to 1502 persons and in 2011 was down to 1244 persons. In that case, famili’s role is needed especially in giving treatment, it’s not only physical treatment but also psychosocial treatment.Objective: to find out the role of the family in the treatment of patients with pulmonary tuberculosis in Gapura Sumenep 2013.Methode: using descriptive research approach of cross sectional. For the processing data precessed by editing, coding, skoring, and tabulating.Result: the result showed that most of respondents including the role of family category is quite (40%) Where the role of a good family caused due to high awareness of families for mutual nurturing and giving health care to sick family members so that they can influence the success of treatment in pulmonary tuberculosis patients.Conclusion: the role of the family about the actions in the treatment of pulmonary tuberculosis patients with pad most respondents included categories quitebas much as (40%)Key word: Family’s role, Treatment, Pulmonary Tuberculosis.